Optimization procedures for enhancement of city breathability using arcade design in a realistic high-rise urban area. (15th August 2017) - Juan, Yu-Hsuan; Yang, An-Shik; Wen, Chih-Yung; Lee, Yee-Ting; Wang, Po-Chun
Abstract: Concern of city breathability has increased in recent project planning activities. Most previous studies in the literature have demonstrated that it is possible to improve urban ventilation efficiency by manipulating the arrangement of buildings with the integration of half open spaces into building configurations. In considering the arcade design which is a conventional type of half open space, this paper first focuses on examining the ventilation performance in a realistic high-rise urban area and its associated city breathability in terms of the ACH* (defined as the ratio of the ACH to a characteristic frequency, determined by the reference velocity of the far upstream free flow divided by the reference building height) with or without incorporating an arcade into the object buildings. On-site measurements are conducted to validate the computational model. Then, the optimization procedures are presented, in which correlations from multivariable regression from our earlier study on generic urban street canyons are applied as the design guidelines for the arcade to maximize the ACH* . Computational fluid dynamics simulations are extended to take into consideration buildings with an arcade of optimum height and width in actual urban canyons to determine the effectiveness of the optimization procedures used to design arcade buildings for enhancing city breathability. Highlights: Arcade design is effective to enhance ventilation in realistic high-rise urban area. On-site measurements were made for validation of the computational model. Procedures were applied to attain optimal arcade design of h  = 4 m and w  = 7.5 m. Results showed efficacy of optimized arcade design to boost city breathability.